Self-Esteem of Students with Learning Difficulties at School - Rahayu1, Elsha; Syamsu, Yusuf (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2023)
Self-esteem is an assessment in the form of self-evaluation of value possessed, as a form of self-defense against the acceptance of positive and negative judgments expressed through attitudes. Low self-esteem that students have can affect life, in terms of social, academic, personal, and career. A student with learning difficulties is someone who shows certain failures as a result of not achieving learning objectives. In this article, the method used in the research literature review aims to be able to provide relevant studies from reliable sources regarding the self-esteem of students with learning difficulties. The problems that students with learning difficulties have are very complex and result from various factors, making them prone to low self-esteem.